CD44+ cells determine fenofibrate-induced microevolution of drug-resistance in prostate cancer cell populations. (2nd October 2020) - Wróbel, Tomasz; Luty, Marcin; Catapano, Jessica; Karnas, Elżbieta; Szczygieł, Małgorzata; Piwowarczyk, Katarzyna; Ryszawy, Damian; Drabik, Grażyna; Zuba-Surma, Ewa; Siedlar, Maciej; Madeja, Zbigniew; Elas, Martyna; et al.
Abstract: Combinations of metabolic blockers (including fenofibrate) with chemotherapeutic drugs interfere with the drug-resistance of prostate cancer cells. However, their effect on cancer stem cells-dependent microevolution of prostate cancer malignancy remains unaddressed. Here, we hypothesize that the combined docetaxel/fenofibrate treatment prompts the selective expansion of cancer stem cells that affects the microevolution of their progenies. Accordingly, we adapted a combined in vitro/in vivo approach to identify biological and therapeutic consequences of this process. Minute subpopulations of docetaxel-resistant CD133 high and/or CD44 high cancer stem cell-like (SCL) cells were found in prostate cancer DU145 and PC3 cell populations. When pretreated with docetaxel, they readily differentiated into docetaxel-resistant CD44 negative "bulk" cells, thus accounting for the microevolution of drug-resistant cell lineages. Combined docetaxel/fenofibrate treatment induced the generation of poly(morpho)nuclear giant cells and drug-resistant CD44 high SCL cells. However, the CD44 negative offspring of docetaxel- and docetaxel/fenofibrate-treated SCLs remained relatively sensitive to the combined treatment, while retaining enhanced resistance to docetaxel. Long-term propagation of drug-resistant SCL-derived lineages in the absence of docetaxel/fenofibrate resulted in their reverse microevolution toward the drug-sensitivity and invasive phenotype. Consequently, prostate tumors were able to recover from the combined docetaxel/fenofibrate stress after the initial arrest of their expansion in vivo. In conclusion, we have confirmed the potential of fenofibrate for the metronomic treatment of drug-resistant prostate tumors. However, docetaxel/fenofibrate-induced selective expansion of hyper-resistant CD44 high SCL prostate cells and their "bulk" progenies prompts the microevolution of prostate tumor drug-resistance. This process can limit the implementation of metabolic chemotherapy in prostate cancer treatment. : Abstract : CD44 + stem cell-related microevolution of prostate cancer drug-resistance under the combined chemotherapeutic/metabolic stress. Combined (DCX)/fenofibrate (FF) treatment induces the formation of polymorphonuclear cells (upper insert) and DCX/FF-resistant CD44 + /CD133 + SCL cells (lower insert) that give rise to DCX- (but not DCX/FF-) "super-resistant" cell populations (right).